In Vitro Activities of Telithromycin, Linezolid, and Quinupristin-Dalfopristin against Streptococcus pneumoniae with Macrolide Resistance Due to Ribosomal Mutations - Farrell, David J. (American Society for Microbiology, 2004)
To date, 86 of 7,746 macrolide-resistant Streptococcus pneumoniae isolates from 1999 to 2002 PROTEKT (Prospective Resistant Organism Tracking and Epidemiology for the Ketolide Telithromycin) surveillance studies were negative for methylase and efflux mechanisms. Mutations in 23S rRNA or the genes encoding riboprotein L4 or L22 were found in 77 of 86 isolates. Six isolates were resistant to quinupristin-dalfopristin and two were resistant to linezolid, while telithromycin demonstrated good activities against all isolates.